IMPLEMENTASI KEBIJAKAN PENGURUSAN SURAT IZIN TEMPAT USAHA DI KECAMATAN NANGA TAMAN KABUPATEN SEKADAU - Nazarius Hendro Ando E.42009064 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2013)
This discussion paper aims to describe the implementation process of the maintenance effort Permit has been granted by the Regent Sekadau Sekadau accordance with decree No. 4 of 2006 on the management of the business location permit. In this study the authors would like to formulate the problem is how the process of implementing the maintenance location permit in District Nanga Sekadau Park District. So the purpose of the study is to describe and analyze the process of implementing management policies in the Business Permit Sub Sekadau Nanga Park District. The authors concluded there are 3 (three) factors that must be traversed affect the successful implementation of policies and Stress Management in the Business Permit Nanga District Park District Sekadau the Organization, Interpretation and Application. The authors concluded that the activity of Clearance Application Permit process was convoluted effort, thus causing the reluctant care of letter location permit. Furthermore, the author gives some advice to the Head Office Nanga Sekadau Park District to provide good service in business administration Permit particularly with regard to the application. Keyword : Stress Management Policy, Business Permit